4 - Sri Lanka on the Verge on non-Violence : Can Violence lead to a Stable Peace ? - Rumana Monzur (Identity, Culture and Politics, 2009)
Years of carnage and destruction turned Sri Lanka- the emerald isle of Tourists’ literature blood red. While trying to determine the conflict structure where the Sri Lankan civil war fits and analyzing the peace building challenges the country will face, one of the useful findings is that the international community is not monolithic and different actors have different assumptions and priorities and have played different roles in the conflict. Now the government has to adopt a humane approach to implement different confidence building measures to that no future Prabhakaran is born and the people have to learn how to arm peace movement i.e. how grief and rage could be turned into courage.